Psycho-Social Stimulation and Food Diversity of Children Detected Stunting - Rahmawati, Dian; Agustin, Lia (Journal of Maternal and Child Health, 2021)
Background: Stunting is a growth failure in children under five due to chronic malnutrition so that children are too short for their age. According to WHO, stunting becomes a public health problem if the prevalence is 20% or more. The prevalence of stunting under five in Indonesia in 2018 was more than 20% so that it became a public health problem and needed to be addressed immediately. Food diversity describes the quality of food for toddlers. Providing a variety of foods will increase the risk of malnutrition, stunting, and disease disorders. Stunting not only has an impact on physical growth but also psychosocial development. This study aimed to analyze whether psychosocial stimulation and food diversity were associated with stunting. Subjects and Method: This research is an observational analytic with a case control approach. The study population was all toddlers aged 24-59 months in Bangkok Village, Gurah, Kediri, East Java, Indonesia, in August 2020. Using the fixed disease sampling technique, a sample of 25 stunting toddlers aged 24-59 months as the case group and 25 non-stunted toddlers as the control group. The dependent variable is the incidence of stunting, while the independent variables are psychosocial stimulation and food diversity. The stunting measurement was carried out based on the TB/U measurement. Measurement of psychosocial stimulation using the HOME (The Home Observation for Measurement of the Environment Revisited) questionnaire and diversity using the IDDS (Individual Dietary Diversity Score) questionnaire. The data collected were analyzed by Chi Square and Fisher's Exact Test. Results: The incidence of stunting was associated with psychosocial (p= o.o31) and food diversity (OR= 12.67; CI 95%= 3.31 to 48.50; p < 0.001). Conclusion: Psychosocial stimulation and food diversity are associated with stunting. Not consuming a variety of foods increases the incidence of stunting 12 times.